De-centring the choreographer: Historically inspired interruptions/disruptions in an exploration between sculpture and movement1. Issue 2 (1st December 2019) - Sarkar, Kaustavi
AbstractThis article reflects the process of choreographic making where the choreographer actively decentres her choreographic choices by collaborating with participating dancers and historical inspirations. It explores the creative potential of archives ‐ a set of temple-sculptures found in eastern India called the Alasa-Kanyas (meaning indolent maidens) ‐ as past evidence of historically marginalized bodies of the temple-dancers, also known as Maharis, in the field of the eastern Indian classical dance form called Odissi. Alasa-Kanya: Sculpture in Odissi (AK), a Practice as Research (PaR) experiment, imbricates the historical and the theoretical in choreographic practice, re-inscribing the archival traces of the Mahari as found in the sculptural traces of the Alasa-Kanyas by an inculcated deconstruction of Odissi dance vocabulary. According to philosopher Jacques Derrida, deconstruction destabilizes the hierarchy between the centres and margins of a given area of knowledge. This experiment questions the hierarchical construction of Odissi dance as technically elevated than Mahari performance. Theoretical deconstruction is complemented by an embodied investigation via structured studio improvisations using the Creative Articulations Process (CAP). Choreographic process and analysis of AK deconstructs the technicity in Odissi movement via engaging with the Alasa-Kanyas or the sculptural archives of the Maharis in Indian temples. In this way, the once marginalized interrupts the dominant historical narratives and disrupts the patriarchal construction of a male centre, in turn questioning the agency of the choreographer in the choreographic process.